2022
DOI: 10.3389/fmolb.2021.758742
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Serum TUG1, LINC00657, miR-9, and miR-106a in Diabetic Patients With and Without Ischemic Stroke

Abstract: Background: Ischemic stroke is one of the serious complications of diabetes. Non-coding RNAs are established as promising biomarkers for diabetes and its complications. The present research investigated the expression profiles of serum TUG1, LINC00657, miR-9, and miR-106a in diabetic patients with and without stroke.Methods: A total of 75 diabetic patients without stroke, 77 patients with stroke, and 71 healthy controls were recruited in the current study. The serum expression levels of TUG1, LINC00657, miR-9,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Previous studies have demonstrated that TUG1 plays an essential role in various ischemic stroke-related procedures [ 27 ]. They have also confirmed that the serum TUG1 level of diabetic patients with ischemic stroke is significantly higher than that of diabetic patients without ischemic stroke, and the serum TUG1 level is positively correlated with the NIHSS score of the patients [ 14 ]. TUG1 rs2240183 may be used as a new biomarker to predict the short-term prognosis of patients with ischemic stroke [ 28 ].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Previous studies have demonstrated that TUG1 plays an essential role in various ischemic stroke-related procedures [ 27 ]. They have also confirmed that the serum TUG1 level of diabetic patients with ischemic stroke is significantly higher than that of diabetic patients without ischemic stroke, and the serum TUG1 level is positively correlated with the NIHSS score of the patients [ 14 ]. TUG1 rs2240183 may be used as a new biomarker to predict the short-term prognosis of patients with ischemic stroke [ 28 ].…”
Section: Discussionmentioning
confidence: 86%
“…More recently, it was reported that TUG1 can regulate angiogenesis in diverse clinical scenarios [ 12 , 13 ]. Abdelaleem et al [ 14 ] found that serum lncRNA TUG1 might be a useful novel molecular biomarker for diabetes complicated by a stroke. Earlier researches suggested that TUG1 may have a vital role in the pathological changes after cerebral infarction [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Strong associations among TUG1, miR-9, LINC00657, and stroke severity were noted, with miR-106a showing a negative correlation. These non-coding RNAs could serve as potential indicators of disease and potential targets for treatment in diabetes stroke patients ( Abdelaleem et al, 2021 ). Diabetes mellitus is marked by β-cell loss and dysfunction, contributing to impaired insulin production and glucose regulation.…”
Section: Tug1 and Diabetesmentioning
confidence: 99%
“…In recent years, the investigation of epigenetic mechanisms has unveiled novel layers of complexity in the origin and advancement of diverse conditions, among them diabetes and its linked complications, mechanisms have a significant role ( Abdelaleem et al, 2021 ). Diabetes mellitus, distinguished by persistent high blood sugar due to compromised insulin function or secretion, poses a worldwide health challenge with increasing occurrence ( Chen et al, 2021 , Bhat et al, 2023a , Bhat et al, 2023b , Bhat et al, 2023c ).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2.Forest plot for the correlation between the concentration of let-7i, miR-9, miR-21, miR-29b, miR-124, miR-124-3p, and NIHSS score; in certain cases, we address separately all reported studies (A) and (B) only studies with reported same miRNA source. References: miR-29b:[47,70,71,75]; let-7i:[54,56]; miR-9:[60,66,72,73]; miR-21:[68,69]; miR-124-3p:[61,63]; miR-124:[57,60,74].…”
mentioning
confidence: 99%